pH-Metric Study on Determination of Metal-Ligand Stability Constants of Some Substituted Isoxazolines - Pawar, N.N.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
The interaction of Cu(II), Co(II), Fe(III), Al(III) and Nd(III) with 3-(2-hydroxy-5-chlorophenyl)-5-(4-methoxy phenyl) isoxazoline (1), 3-(2-hydroxy-3-nitro-5-chlorophenyl)-5-(4-methoxy phenyl) isoxazoline (2) and 3-(2-hydroxy-3-bromo-5-chlorophenyl)-5-(4-methoxy phenyl) isoxazoline (3) have been studied by Calvin-Bjerrum titration technique in media of 70% dioxane-water mixture at 0.1 M ionic strength and at (30 ± 0.1ºC) temperature. It is observed that the formation of 1 : 1 and 1 : 2 complexes is occurring simultaneously.